A reproducible and replicable approach for harmonizing Landsat-8 and Sentinel-2 images - Marujo, Rennan de Freitas Bezerra; Carlos, Felipe Menino; Costa, Raphael Willian da; Arcanjo, Jeferson de Souza; Fronza, José Guilherme; Soares, Anderson Reis; Queiroz, Gilberto Ribeiro de; Ferreira, Karine Reis (Frontiers in Remote Sensing, 2023)
Clouds and cloud shadows significantly impact optical remote sensing. Combining images from different sources can help to obtain more frequently time series of the Earth's surface. Nevertheless, sensor differences must be accounted and treated before combining images from multiple sensors. Even after geometric correction, inter-calibration and band pass, disparities in image measurements can persist. One potential factor contributing to this phenomenon is directional effects. Bidirectional reflectance distribution function (BRDF) corrections emerge as an optional processing to soften differences in surface reflectance (SR) measurements, where the c-factor is one of the available options for this task. The c-factor efficiency is well proven for medium spatial resolution products. However, its use should be restricted to images from sensors with a narrow view, since it performs subtle changes in the processed images. Despite being accessible and well-documented, there are currently limited open tools for users to independently process their images. Here we implemented the required tools to generate a Nadir BRDF Adjusted Surface Reflectance (NBAR) product through the c-factor approach, as well as evaluate them for a study area using Landsat-8 and Sentinel-2 images. Several comparisons were conducted to verify the SR and NBAR differences. Initially, a single sensor approach was adopted and later a multi-source approach. Notably, NBAR products exhibit fewer disparities compared to SR products (prior to BRDF corrections). The results reinforce that the c-factor can be used to improve time series compatibility and, most importantly, provides the tools to allow users to generate the NBAR products themselves.